Wacana dan Praktik Moderasi Beragama pada Sekolah Menengah Atas di Kota Metro - Nety Hermawati; Siti Mustaghfiroh; Lisa Safitri; Sri Furyani (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2023)
A moderate understanding of religion is a necessity for all Indonesians living side by side with various religions. Misunderstandings and extremes in understanding religious teachings can be a source of problems that can then lead to horizontal conflicts in society. An attitude of acknowledging the existence of others, respecting and respecting each other's differences, and not imposing desires in a violent way for the sake of creating harmony between religious communities. Indonesia as a country with religious diversity has the potential for friction between religious communities. This service is implemented at SMKN 1 Metro in order to increase knowledge, understanding, and moderation among students. By using the service learning method, this service tries to close the distance between campuses represented by lecturers and students who have problems in the community. The results were previously 14.5 percent of students did not understand religious moderation, after understanding religious moderation then tested through a post test and the results were 100 percent of students knew religious moderation. Students who answered religious moderation means being in religion has increased to 89.3 percent. Even as many as 20 percent previously considered religious moderation as an extreme attitude in religion no longer exists.